Semantic Analysis In The Lyrics Of Lenka’s Songs - Windy Sasri (Universitas Muhammadiyah Sumatera Utara, 2021)
The research deals with the study of semantic analysis in the lyrics of Lenka‟s song, the descriptivr qualitative method was applied in this research. From the analysis it was found that there were four types of metaphor found in Lenka‟s songs. They were Anthropomorphic metaphor, Synesthetic metaphor, Abstract to concrete metaphor, and Animal metaphor. The total number of metaphor were 11 lyrics, the anthropomorphic metaphor were 8 lyrics, abstract to concrete metaphor were 7 lyrics, and the last synesthtic metaphor was 1 lyric. The data of this research was in the form of the written text or transcription in the Lenka‟s song lyrics entitled Lucky, Everything at Once, and The Show. The research was applied descriptive qualitative method. There were 27 lyrics that were analyze through the application of Ullman theory were data reduction, data presentation, and conclusion drawing or verification were carried out significantly. The research result showed that found (1) there were 4 types of metaphor found in the 3 songs of Lenka. They were Anthropomorphic, Synesthetic, Abstract to concrete, and Animal metaphor. That the dominant type found in those songs was abstract to concrete metaphor. It was 44.4%, it was dominantly used the combination of adjective plus noun as phrase. (2) The way metaphor attached to the root was based on the meaning of the words itself in the sentences. (3) The reason why the metaphor used in the Lenka‟s songs were metaphor was one style of language that is often used in daily life, both orally and in writing. Keywords: Semantic, Metaphor, Ullman.